(untitled) (Journal of Management and Social Sciences, 2023)
Work-life balance has become an issue of great concern to various employees in both private and public sectors. This study examines the impact of work-life balance on job performance among employees of selected private universities in Osun State. The specific objectives of the study are to assess the significant impact of organizational support on employee job satisfaction, and examined the significant impact of leisure-time management on employee job commitment, which is also in line with the research questions and hypotheses. Descriptive survey research design is adopted, the population of the study is 210 academic staff of two selected private universities in Osun State and sample size was equivalent to the number of the research population without the use of any formula since the population of the study is small. Data for this study was generated from primary source using structured questionnaire from 210 academic staff of Fountain University and Redeemer’s University in Osun State. The data obtained was analyzed using regression analysis with the aid of SPSS package. The findings from the study reveal that organizational support have significant influence on employees’ job satisfaction (r2=0.416, p<0.05). the study also reveals that leisure-time management has significant impact on employee job commitment (r2=0.546, p<0.05). The study concludes that organizational support and leisure-time management has significant impact on employee’s job performance in selected private universities. Therefore, the study recommends that management should design policies that consider the job satisfaction of employees, balance work and social time.